2010
DOI: 10.1128/ec.00197-09
|View full text |Cite
|
Sign up to set email alerts
|

Suggestive Evidence for Darwinian Selection against Asparagine-Linked Glycans of Plasmodium falciparum and Toxoplasma gondii

Abstract: We are interested in asparagine-linked glycans (N-glycans) of Plasmodium falciparum and Toxoplasma gondii, because their N-glycan structures have been controversial and because we hypothesize that there might be selection against N-glycans in nucleus-encoded proteins that must pass through the endoplasmic reticulum (ER) prior to threading into the apicoplast. In support of our hypothesis, we observed the following. First, in protists with apicoplasts, there is extensive secondary loss of Alg enzymes that make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 58 publications
4
109
0
Order By: Relevance
“…2 and Table 2). The sugar nucleotides detected in the parasite agree well with the monosaccharide contents of known glycoconjugates in P. falciparum consisting of glucosamine (derived from GlcNAc) and Man residues present in GPI anchors and N-glycans (11,14). Furthermore, the detection of UDP-GlcNAc, UDP-Glc, GDP-Man, and GDP-Fuc is consistent with the presence of known or candidate sugar nucleotide biosynthetic enzymes encoded in the genome of P. falciparum (25).…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…2 and Table 2). The sugar nucleotides detected in the parasite agree well with the monosaccharide contents of known glycoconjugates in P. falciparum consisting of glucosamine (derived from GlcNAc) and Man residues present in GPI anchors and N-glycans (11,14). Furthermore, the detection of UDP-GlcNAc, UDP-Glc, GDP-Man, and GDP-Fuc is consistent with the presence of known or candidate sugar nucleotide biosynthetic enzymes encoded in the genome of P. falciparum (25).…”
Section: Resultssupporting
confidence: 67%
“…In the particular case of the malaria parasite, glycan structures associated with the parasite itself appear to be limited to GPI anchors (11,51) and the recently described N-glycans (14). This seems to confirm the general trend of Plasmodium parasites to reduce several metabolic and biosynthetic pathways and reflects the process of evolving toward a parasitic niche (52).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The amount of N-linked carbohydrates in whole parasite proteins is approximately 6% compared with the GPI anchors attached to proteins based on radioactive GlcN incorporated into the proteins (Gowda et al, 1997). Bushkin et al (2010) suggested that the occupation of N-glycan sites is markedly reduced in apicoplast proteins versus some secreted proteins in Plasmodium. Clearly, more work has to be done in order to elucidate the nature and purpose of N-linked glycoproteins in Plasmodium.…”
Section: Detection Of N-linked Glycoproteins In P Falciparummentioning
confidence: 99%